Bis(thien‐2‐yl)‐2, 1, 3‐benzothiadiazole‐diketopyrrolopyrrole‐based acceptor–acceptor conjugated polymers: Design, synthesis, and the synergistic effect of the substituent on their solar cell properties. Issue 43 (27th April 2020) - Du, Junping; Feng, Shanshan; Qin, Pengju; Xu, Liancai; Zhu, Wenjing; Huang, Jiang
Abstract: Three acceptor–acceptor conjugated copolymers (TBT‐DPP, FTBT‐DPP, and HFTBT‐DPP ) with different substituent groups have been synthesized with palladium‐catalyzed Stille coupling condensation polymerization assisted with microwave. Polymer solar cells (PSCs) based on these copolymers as the electron donors and PC71BM as the acceptor have been fabricated. The synergistic effect of the substituent between two fluorine atoms and hexyl alkyl chains in bis(thien‐2‐yl)‐2, 1, 3‐benzothiadiazole fragment on their solar cell properties has been investigated. Both the fluorine atoms and the synergistic effect can improve the solubility of the polymers effectively while the excellent thermal stability properties are still retained. Two fluorine atoms (polymer FTBT‐DPP ) increased the power conversion efficiency of the PSCs twice compared with TBT‐DPP (without substituent). The synergistic effect (polymer HFTBT‐DPP ) decreased that seriously to zero. Density function theory calculations showed that the conjugation level of the polymer backbone is one of key factors. It demonstrates that the synergistic effect of fluorine atoms and alkyl chains in the same fragment does not always work well in improving the PSCs performance. Abstract :